Identiti Dalam Industri Filem VCD Iban - Micheal Baran, Paoh (Universiti Malaysia Sarawak, (UNIMAS), 2007)
Identity is an important element in a film industry. This uniqueness in filmmaking helps to differentiate one film industry from the other. In Sarawak, the Than VCD Movie Industry is still new. To be able to compete in the film industry in Malaysia, the Than Movie Industry needs to move forward with its own ingredient to differentiate itself from the other films. This study aims to look at identity in Than VCD movies by focusing on three production companies Golden Pearl Sdn Bhd, TBC Sdn Bhd, and LUH Sdn Bhd. This research methods used consist of in-depth interviews and film analysis. The result of this study shows that there is no strength of identity in Than VCD movies as the industry is still motivated by business profits